Dual control of flagellar synthesis and exopolysaccharide production by FlbD-FliX class II regulatory proteins in Bradyrhizobium diazoefficiens - Dardis, Carolina (2021)
Bradyrhizobium diazoefficiens, the N2-fixing symbiont of soybean, has two independent flagellar systems: a single subpolar flagellum and several lateral flagella. Each flagellum is a very complex organelle composed of 30 to 40 different proteins located inside and outside the cell whereby flagellar gene expression must be tightly controlled. Such control is achieved by a hierarchy of regulators that ensure the timing of synthesis and the allocation of the different flagellar substructures. Previously, we analyzed the gene organization, expression, and function of the lateral flagellar system. Here, we studied the role of the response regulator FlbD and its trans-acting regulator FliX in the regulation of subpolar flagellar genes. We found that the LP-ring, distal rod, and hook of the subpolar flagellum were tightly controlled by FlbD and FliX. Furthermore, we obtained evidence for the existence of cross-regulation between these gene products and the expression of LafR, the master regulator of lateral flagella. In addition, we observed that extracellular polysaccharide production and biofilm formation also responded to these flagellar regulators. In this regard, FlbD might contribute to the switch between the planktonic and sessile states. Importance: Most environmental bacteria switch between two free-living states: planktonic, in which individual cells swim propelled by flagella, and sessile, in which bacteria form biofilms. Apart from being essential for locomotion, the flagellum has accessory functions during biofilm formation. The synthesis of flagella is a highly regulated process, and coordination with accessory functions requires the interconnection of various regulatory networks. Here, we show the role of class II regulators involved in the synthesis of the B. diazoefficiens subpolar flagellum and their possible participation in cross-regulation with the lateral flagellar system and exopolysaccharide production. These findings highlight the coordination of the synthetic processes of external structures, such as subpolar and lateral flagella, with exopolysaccharides, which are the main component of the biofilm matrix.